2018
DOI: 10.5194/amt-2018-19
|View full text |Cite
Preprint
|
Sign up to set email alerts
|

Airborne wind lidar observations over the North Atlantic in 2016 for the pre-launch validation of the satellite mission Aeolus

Abstract: The paper also highlights the relevance of accurate ground detection for the Rayleigh and Mie response calibration and wind retrieval. Using a detection scheme developed for the NAWDEX campaign, the obtained ground return signals are exploited for the correction of systematic wind errors. Validation of the instrument performance and retrieval algorithms was conducted by comparison with DLR's coherent wind lidar which was operated in parallel, showing a systematic error of the A2D LOS winds of less than 0.5 m·s… Show more

Help me understand this report
View published versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
18
0
1

Year Published

2018
2018
2022
2022

Publication Types

Select...
5
1

Relationship

2
4

Authors

Journals

citations
Cited by 10 publications
(20 citation statements)
references
References 27 publications
(30 reference statements)
1
18
0
1
Order By: Relevance
“…This result is consistent with previous verifications of the DWLmeasured wind speeds with dropsonde data [20,27]. Other studies [28][29][30][31] have shown comparisons of DWL data to dropsonde data that are in better agreement than with our study (i.e., smaller RMSE). This is most likely due to the fact that TCs have a highly variable wind field, and the different measurement volumes had different wind speeds in the comparison.…”
Section: Resultssupporting
confidence: 93%
“…This result is consistent with previous verifications of the DWLmeasured wind speeds with dropsonde data [20,27]. Other studies [28][29][30][31] have shown comparisons of DWL data to dropsonde data that are in better agreement than with our study (i.e., smaller RMSE). This is most likely due to the fact that TCs have a highly variable wind field, and the different measurement volumes had different wind speeds in the comparison.…”
Section: Resultssupporting
confidence: 93%
“…Already several years before the launch, an airborne prototype of the Aeolus payload, the ALADIN Airborne Demonstrator (A2D), was developed at DLR. Owing to its representative design and operating principle, the A2D provides valuable information on the wind measurement strategies of the satellite instrument as well as on the optimization of the wind retrieval and related quality-control algorithms [10,11]. In November 2018, the first airborne validation campaign after launch was carried out from the airbase in Oberpfaffenhofen, Germany.…”
Section: First Airborne Validation Resultsmentioning
confidence: 99%
“…Following WindVal III in late 2018, two additional airborne validation campaigns were conducted within the first year of the operational phase of Aeolus. Whereas the AVATARE campaign (Airborne VAlidation Through Airborne lidaRs in Europe) was again carried out from Oberpfaffenhofen, Germany, in May/June 2019, AVATARI (Airborne VAlidation Through Airborne lidaRs in Iceland), performed in September 2019, had its air base in Keflavík, Iceland, which was also the location of the WindVal II cam-paign in 2016 prior to the launch (Lux et al, 2018;Schäfler et al, 2018). The two campaigns not only considerably extended the available dataset to validate Aeolus wind observations in different geographical regions and under different atmospheric conditions in terms of cloud types and dynamics but also served to assess the accuracy and precision of the Aeolus wind product in different phases of the mission.…”
Section: Overview Of Validation Campaigns and Datasetsmentioning
confidence: 99%
“…The A2D was developed by the European Aeronautic Defence and Space (EADS) Astrium (now Airbus Defence and Space) in cooperation with the DLR in the early 2000s. Its design and operating principle were extensively described in several previous publications (Paffrath et al, 2009;Reitebuch et al, 2009;Lux et al, 2018Lux et al, , 2020a. Therefore, only a brief description is provided here.…”
Section: Avatarimentioning
confidence: 99%
See 1 more Smart Citation